An adaptable model for growth and/or shrinkage of droplets in the respiratory tract during inhalation of aqueous particles. (March 2016) - Grasmeijer, Niels; Frijlink, Henderik W.; Hinrichs, Wouter L.J.
Abstract: The site of deposition of pulmonary delivered aerosols is dependent on the aerosol׳s droplet size distribution, which may change during inhalation. The aim of this study was to develop a freely accessible and adaptable model that describes the growth (due to condensation) and shrinkage (due to evaporation) of inhaled droplets as a function of the distance from the airway wall during various inhalation conditions, for a laminar flow scenario. This was achieved by developing a model with which the evaporation of water from a droplet surface or condensation of water onto the droplet surface can be calculated. This model was then applied to a second model that describes the heat and mass transfer from the airway wall to the inhaled aerosol. The latter was based on the Weibel model. It was found that the growth and shrinkage of inhaled droplets markedly differs, depending on the distance from the airway wall. Droplets near the wall start to grow immediately due to fast water vapor transfer from the wall to the cold inhaled air. This growth continues until the air reaches body temperature and is fully saturated. However, droplets in the center of the airway first evaporate partly, due to a delay in water vapor transfer from the airway wall, before they start to grow. Depending on the conditions during inhalation, the droplet size distribution can widen considerably, which may affect the lung deposition and thereby the efficacy of the inhalation therapy. In conclusion, the model was able to show the effect of the conditions in the respiratory tract on the growth and shrinkage of inhaled droplets during standard inhalation conditions. Future developments can be aimed at expanding the model to include turbulent flow and hygroscopic growth, to improve the accuracy of the model and make it applicable to both droplets of solutions and dry particles. Highlights: A freely available model was developed for inhaled droplet growth and/or shrinkage. Droplet size change was simulated for laminar flow under various conditions. Droplets close to airway wall only grow; in the center they first shrink, then grow. Change in droplet size distribution width depends on conditions during inhalation. The model can be adapted, e.g. to add turbulent flow and hygroscopic growth effects.